Short-Selling, Leverage and Systemic Risk - Amelia Pais; Philip A. Stork (Tinbergen Institute, 2013)
During the Global Financial Crisis, regulators imposed short-selling bans to protect financial institutions. The rationale behind the bans was that bear raids, driven by short-sellers, would increase the individual and systemic risk of financial institutions, especially for institutions with high leverage. This study uses Extreme Value Theory to estimate the effect of short-selling on financial institutions individual and systemic risks in France, Italy and Spain; it also analyses the relationship between financial institutions leverage and short-selling. The results show that short-sellers appear to specifically target institutions with lower capital levels. Furthermore, institutions risk-levels and changes in short-selling positions tend to move in tandem.
Keywords: C14; G01; G15; G21; 330; bear raids; short-selling bans; financial institutions risk; systemic risk; leverage capital requirements; Extreme Value Theory